SUITABILITY OF CU-AND NI-CONTAINING GALVANIC FINAL TAILINGS FOR PROCESSING IN ADDITION ALLOYS FOR IRON-CARBON METAL - A. S. Panasugin; S. V. Grigorjev; V. A. Lomonosov; D. P. Mihalap; S. A. Panasugin; R. V. Degtjarev (Литьë и металлургия, 2011)
The problems of galvanic production waste recovery, conditions, influencing on the final tailings composition, influence of the chemical composition of final tailings on the ways of their recovery are examined.